A computational method to answer semantic questions with constraints - Mohd Sharef, Nurfadhlina; Mohd Noah, Shahrul Azman; Abdul Kadir, Rabiah; Azman, Azreen (UUM College of Arts and Sciences, Universiti Utara Malaysia, 2013)
Semantic question answering is a discipline that allows the development of smart systems through its reasoning and natural language understanding capability. Knowledge is stored based on representation format such as ontology. However, querying these knowledge requires understanding of the knowledge structure and demands the user to be equipped with the formal query construction skill. This will definitely hinder the development of this area. Therefore this paper addresses the translation model of constraints-typed questions. We focus on the components that relate to constraints-typed question answering and propose a computational model for the translation. These figures indicate promising development in this problem and should encourage more alternative methods in the same direction.